Traces of the Ramayana and Mahabharata in Javanese and Malay Literature - Molen, W. van der (Willem), 1952-; Ding, Choo Ming (Nalanda-Sriwijaya series, 2018)
Local renderings of the two Indian epics Ramayana and Mahabharata in Malay and Javanese literature have existed since around the ninth and tenth centuries. In the following centuries new versions were created alongside the old ones, and these opened up interesting new directions. They questioned the views of previous versions and laid different accents, in a continuous process of modernization and adaptation, successfully satisfying the curiosity of their audiences for more than a thousand years. Much of this history is still unclear. For a long time, scholarly research made little progress, due to its preoccupation with problems of origin. The present volume, going beyond identifying sources, analyses the socio-literary contexts and ideological foundations of seemingly similar contents and concepts in different periods; it examines the literary functions of borrowing and intertextual referencing, and calls upon the visual arts to illustrate the independent character of the epic tradition in Southeast Asia.